Prevalence of syphilis, gonorrhoea and chlamydia in women in Fiji, the Federated States of Micronesia, Papua New Guinea and Samoa, 1995-2017: Spectrum-STI model estimates - Takeshi Nishijima; Devina Nand; Nefertti David; Mathias Bauri; Robert Carney; Khin Cho Win Htin; Ye Yu Shwe; Anup Gurung; Guy Mahiane; Naoko Ishikawa; Melanie M Taylor; Eline L Korenromp (World Health Organization Regional Office for the Western Pacific, 2020)
Objectives: To estimate prevalence levels of and time trends for active syphilis, gonorrhoea and chlamydia in women aged 15-49 years in four countries in the Pacific (Fiji, the Federated States of Micronesia [FSM], Papua New Guinea [PNG] and Samoa) to inform surveillance and control strategies for sexually transmitted infections (STIs). Methods: The Spectrum-STI model was fitted to data from prevalence surveys and screenings of adult female populations collected during 1995−2017 and adjusted for diagnostic test performance and to account for undersampled high-risk populations. For chlamydia and gonorrhoea, data were further adjusted for age and differences between urban and rural areas. Results: Prevalence levels were estimated as a percentage (95% confidence interval). In 2017, active syphilis prevalence was estimated in Fiji at 3.89% (2.82 to 5.06), in FSM at 1.48% (0.93 to 2.16), in PNG at 3.91% (1.67 to 7.24) and in Samoa at 0.16% (0.07 to 0.37). For gonorrhoea, the prevalence in Fiji was 1.63% (0.50 to 3.87); in FSM it was 1.59% (0.49 to 3.58); in PNG it was 11.0% (7.25 to 16.1); and in Samoa it was 1.61% (1.17 to 2.19). The prevalence of chlamydia in Fiji was 24.1% (16.5 to 32.7); in FSM it was 23.9% (18.5 to 30.6); in PNG it was 14.8% (7.39 to 24.7); and in Samoa it was 30.6% (26.8 to 35.0). For each specific disease within each country, the 95% confidence intervals overlapped for 2000 and 2017, although in PNG the 2017 estimates for all three STIs were below the 2000 estimates. These patterns were robust in the sensitivity analyses. Discussion: This study demonstrated a persistently high prevalence of three major bacterial STIs across four countries in WHO's Western Pacific Region during nearly two decades. Further strengthening of strategies to control and prevent STIs is warranted.